2007
DOI: 10.1097/01.brs.0000254109.12449.6c
|View full text |Cite
|
Sign up to set email alerts
|

Level of Evidence in Spine Compared to Other Orthopedic Journals

Abstract: Spine publishes clinical studies with levels of evidence comparable to the 2 orthopedic journals with similar impact factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 11 publications
(8 reference statements)
6
37
0
Order By: Relevance
“…An accurate identification rate (77% and 83%), with a low incidence of misclassification (4% to 5% leading to an inappropriate increase in quality) indicates that LOE is a concept with which faculty and residents are conversant. Our results are consistent with those of other studies that show substantial or better agreement when grading LOE, regardless of experience [2,4,17,32]. In contrast, Schmidt et al [21] found substantial inconsistency and poor agreement between different observers when grading the LOE of presentations at the 2007 AAOS Annual Meeting.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…An accurate identification rate (77% and 83%), with a low incidence of misclassification (4% to 5% leading to an inappropriate increase in quality) indicates that LOE is a concept with which faculty and residents are conversant. Our results are consistent with those of other studies that show substantial or better agreement when grading LOE, regardless of experience [2,4,17,32]. In contrast, Schmidt et al [21] found substantial inconsistency and poor agreement between different observers when grading the LOE of presentations at the 2007 AAOS Annual Meeting.…”
Section: Discussionsupporting
confidence: 90%
“…However, while the proportion of these studies has improved significantly with time, there remains a predominance of Level III and IV studies. This finding is consistent with results from other studies in the orthopaedic literature [4,17,27,32]. Although there is value in these lower-quality studies, higher-quality studies generally are better at removing bias, isolating confounders, and providing reliable data for further clinical practice.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations